THE INSPECTION AND THE ANALYSIS OF DISPLACEMENTS ON MOBILE SUPPORTING PARTS OF BEAMS FRAMEWORKS OF RAILWAY BRIDGE - Tarasenko, V. P.; Huk, L. M.; Odrinskiy, H. M. (Science and Transport Progress, 2010)
The results of inspection of supporting parts, the calculation of setting of mobile supporting parts at erecting of spans and detecting of deformations of supports on the additional displacements on mobile supporting parts are presented in the article.